A protein domain conserved between yeast MCM1 and human SRF directs ternary complex formation. - Mueller, C G (1991)
MCM1 and SRF bind to the same DNA sequence and form ternary complexes with STE12 and p62TCF, respectively. We show that in gel retardation assays, MCM1 recruits both ternary complex factors whereas SRF interacts only with p62TCF. A protein domain of 90 amino acids, shared by MCM1 and SRF, was found to be sufficient for ternary complex formation. The domain is also required for dimerization and DNA binding. Similar regions are found in other proteins, such as ARG80, Deficiens and Agamous. ARG80 and Agamous exhibit similar DNA binding specificities but do not interact with either STE12 or p62TCF. By exchanging three residues of ARG80 with those of corresponding positions in SRF (residues 198, 200 and 203), the ARG80 protein acquires the ability to recruit p62TCF into a ternary complex. Likewise, the substitution of four SRF amino acids by MCM1-derived residues (amino acids 73, 75, 77 and 78) confers on SRF the ability to interact with STE12. Thus, we have identified specific amino acids in MCM1 and SRF that are critical for ternary complex formation and which map to equivalent positions within the shared domains. Therefore, the structural basis for specific protein-protein interaction appears to be conserved in evolution between a class of transcription factors.